Unraveling the immune response in optic nerve injury: implications for retinal ganglion cell protection - Xu, Kexin; Yu, Lu; Zhang, Ningzhi; Dong, Min; Xing, Yiqiao; Yang, Ning (Frontiers in Immunology, 2025)
Optic nerve injury (ONI) initiates complex immune responses that can act as a “double-edged sword,” promoting either neuroprotection or neurodegeneration of retinal ganglion cells (RGCs). In this review, we integrate evidence on both innate and adaptive immunity in ONI, emphasizing the dual roles of microglia, Müller cells, astrocytes, T and B lymphocytes, and the complement system. While glial activation and blood–retina barrier breakdown are critical determinants of local inflammation, T-cell response, which are shaped by subset composition, antigen specificity, and checkpoint signaling, can further shift the balance between repair and injury. Recent advances, including single-cell and spatial transcriptomic analyses, as well as experimental modulation of immune checkpoints, reveal new opportunities—such as precise immune mapping, checkpoint-targeted neuroprotection, and gene-based immunoregulation—but also persistent challenges, including the need to clarify the spatiotemporal dynamics of immune activity, overcome interspecies differences between rodent and human models, and ensure the safety of immunomodulatory strategies in the immune-privileged eye. By applying the “double-edged sword framework” consistently across these immune mechanisms, we highlight how cellular context and timing determine divergent outcomes. Finally, we discuss emerging approaches such as regulatory T-cell enhancement, targeted inhibition of complement overactivation, senolytics, and gene-editing interventions, outlining translational perspectives for immune-guided neuroprotection in ONI.